1999
DOI: 10.1074/jbc.274.19.13181
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Antimicrobial and Hemolytic Activities in Cyclic Peptide Diastereomers by Systematic Alterations in Amphipathicity

Abstract: We have investigated the role of amphipathicity in a homologous series of head-to-tail cyclic antimicrobial peptides in efforts to delineate features resulting in high antimicrobial activity coupled with low hemolytic activity (i.e. a high therapeutic index). The peptide GS14, cyclo(VKLKVd-YPLKVKLd-YP), designed on the basis of gramicidin S (GS), exists in a preformed highly amphipathic ␤-sheet conformation and was used as the base compound for this study. Fourteen diastereomers of GS14 were synthesized; each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
243
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(261 citation statements)
references
References 41 publications
(77 reference statements)
14
243
1
Order By: Relevance
“…7B). A similar pattern of behavior was reported in studies of other analogs of GS14 (6,8,18,19). The possible basis of these and other aspects of the behavior of these peptides are explored under "Discussion."…”
Section: Circular Dichroism Spectroscopic Studies-illustrated Insupporting
confidence: 58%
See 2 more Smart Citations
“…7B). A similar pattern of behavior was reported in studies of other analogs of GS14 (6,8,18,19). The possible basis of these and other aspects of the behavior of these peptides are explored under "Discussion."…”
Section: Circular Dichroism Spectroscopic Studies-illustrated Insupporting
confidence: 58%
“…GS14dK4) usually exhibit antimicrobial activity comparable with that of GS itself but are considerably less hemolytic (8,21). Like GS, these materials are also targeted against lipid bilayer membranes, but they exhibit an enhanced capacity to discriminate between bacterial and animal cell membranes (8,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4) although it is generally assumed that the principal target of GS is the membrane lipid bilayer rather than the protein components. Recent studies have shown that structural analogs of GS can be designed with markedly reduced hemolytic activity and enhanced microbial activity, suggesting the possibility of GS derivatives as potent oral or injectable broad-spectrum antibiotics [9,[20][21][22]. Our finding would provide a new insight into the molecular design and development of novel GS-based antibiotics (see Fig.…”
Section: Effects Of Gs On E Coli Respiratory Enzymes In Intact Membrmentioning
confidence: 61%
“…From the screening of hundreds of natural antibiotics in the Kitasato Institute for Life Sciences Chemical Library [19], we found the inhibitory activity of GS for Escherichia coli cytochrome bd. Recent studies have shown that GS analogs can be designed with the markedly improved therapeutic index, suggesting the possibility of GS derivatives as potent broad-spectrum antibiotics [9,[20][21][22]. Our finding would provide a new insight into molecular design and development of new GS analogs.…”
Section: Introductionmentioning
confidence: 56%